COMPARISON OF RADIATION DOSE IN HSG WITH MAGNIFICATION FACTOR IN FLUOROSCOPY - MS. MS.SUSANNA PRADHAN,; MR. SURESH SUKUMAR, (International Journal of Pharma and Bio Sciences, 2016)
Our main aim of this study was a comparison of radiation dose in HSG with magnification factor. The study was carried on total 38 female patients fulfilling the inclusion criteria who had been suggested for HSG procedure. Among this total population they were divided in four groups according to their BMI. Patient with normal BMI was in group 1, underweight in group2, overweight in group3 and obese in group 4. 24 patients were in group one and were divided 12 each for MF 1 and 2. 5 patients was in group2 and group 3 and were divided into 3 and 2 for MF 1and 2 respectively. Similarly 4 patients were in group4 and were divided into 2 in each MF. Pelvic measurement was taken for each patient prior to the procedure. By using lottery method we selected the magnification factor for each patient and proceeded with the procedure. Exposure was done with intermittent fluoroscopy Data was collected from the dose information stored in the Iconos system. Data was collected only from two exposures and fluoro information was ignored. Performing statistical analysis on group one i.e. with 24 patients, 12 patients with each MF 1 and 2. We carried an independent test on group 1 patients and keeping P value 0.05, we found that the p value was to be 0.004, so this study shows that there is a significance difference in the average radiation dose between magnification factor 1 and 2.